Effect of Withania somnifera leaf extracts as antibacterial agent against multidrug resistant bacteria - Rinku K. Chandoria; Hotam Singh Chaudhary; Alka Yadav; Abhinav Gupta; Jay Prakash Yadav; Anju Rawat Shrivastava (International Journal of Phytomedicine, 2012)
Objective: This study was designed to examine the phytochemical composition and to evaluate antibacterial potential of Withania Somnifera leaf against multidrug resistant bacteria & FT-IR Spectra of different bioactive compounds. Materials and Methods: Toluene, ethanol, and aqueous extracts of W. Somnifera (leaves) were subjected for in vitro antibacterial activity using agar well diffusion against different bacteria of clinical relevance including multi-drug resistant methicillin resistant Staphylococcus aureus (MRSA) and vancomycin resistant Enterococcus (VRE) sps. Results: The toluene extract resulted maximal active as antibacterial agent and found significantly higher active than aqueous extract (P<0.05). The difference between antibacterial activities of toluene and ethanol or ethanol and aqueous extract was statistically non significant (P>0.05). The maximum activity was observed against Staphylococcus aureus. The extracts (at least one) also showed antibacterial activity against Bacillus cereus, coagulase negative staphylococcus, Streptococcus pneumoinae, Shigella dysenteriae, Methicillin resistant Staphylococcus aureus (MRSA) and vancomycin resistant Enterococcus (VRE) sps. Minimum inhibitory concentrations of plant extract were found in the ranges of 0.156mg/ml to 0.625mg/ml for test strains. Phytochemical analyses revealed the presence of various metabolites like phlobtannins, tannins, steroids and alkaloids which may contribute for the antimicrobial action of leaves extract of W. Somnifera. The partial characterization of the crude extracts by IR spectral analysis revealed the possible presence of different bioactive compounds in the extracts. Conclusion: The leaves of W. Somnifera showed promising antibacterial activity against various clinically important bacteria and multidrug resistant MRSA and VRE